Antimicrobial Effect of Copper Nanoparticles on Relevant Supragingival Oral Bacteria - Quiroz-Muñoz, M (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Copper nanoparticles (Cu NPs) show promise in dentistry for combating bacterial dysbiosis and tooth decay. Understanding their effects on commensal versus pathogenic bacteria is vital for maintaining oral health balance. While Cu NPs demonstrate antibacterial properties against various oral bacteria, including common pathogens associated with tooth decay, their impact on commensal bacteria requires careful examination. In our work, we analyzed three types of Cu NPs for their effects on the growth, viability, and biofilm formation of representative caries-associated and commensal oral bacteria. S. sanguinis showed high tolerance to all Cu NPs, while L. rhamnosus was highly sensitive. Oxide-Cu NPs exhibited a stronger inhibitory effect on pathobionts compared with commensal bacteria. Moreover, the biofilm formation of the key cariogenic bacteria S. mutans was reduced, with minimal negative effects on commensal species’ biofilm formation. All our results showed that CuO nanoparticles (CuO NPs) exhibit reduced toxicity toward commensal bacteria growth and development but have a strong impact on pathogens. This suggests their potential for targeted treatments against pathogenic bacteria, which could help in maintaining the balance of the oral bacterial community. © 2024 by the authors.